Analisis similarity dan korespondensi terhadap restoran cepat saji menggunakan pendekatan Multidimensional Scaling dan Correspondence Analysis - Amalia, Wahyuni; Oktavia, Nurike (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The similarity of a business can be a threat if not handled properly. One type of business with a fairly high level of similarity and competitors is fast food restaurants. This study compared 8 fast food restaurants that have similar products and services in order to see the level of similarity and variables that influence the fast food restaurant. There were 55 respondents who had filled out the questionnaire. Based on the results of the analysis using Multidimensional scaling, it can be seen that fast food restaurants have similarities viewed from the distance on the position map. Wendy has similarities with A&W, with a distance of 0.39, Hoka-hoka Bento has similarities with Yoshinoya with a distance of 0.535, KFC is closer to A&W, Burger King is closer to McD, Richeese with KFC, and McD is closer to A&W. Meanwhile, from the perceptual map, it can be seen the advantages of each restaurant such as McD is superior in the delivery service variable and KFC is superior in terms of price